Effects of ergogenic training methods on aerobic capacities of junior swimmers - Solomatin, V. R.; Voytenko, Y. L.; Egorov, A. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to rate benefits of the systemic hyper-hypoxic training with the special respiratory system being applied to improve the aerobic capacities of 15-17 years-old swimmers in the pre-season. Conclusion. The special hyper-hypoxic training exercises using the respiratory system in the pre-season training cycle were provided efficient as verified by the expressed cumulative effects of the training process in general and notable growth of the competitive success rates in particular.